EFFECT OF OTUD3 KNOCKOUT ON THE EXPRESSION OF CONNEXIN 43 IN NEURAL STEM CELLS - XU Tongying, JIAO Qian, JIANG Hong (精准医学杂志, 2023)
Objective To investigate the effect of OTUD3 knockout on the expression of connexin 43 (Cx43) in neural stem cells (NSCs). Methods Brain cortex tissue protein was isolated and extracted from wild-type (WT) and OTUD3-/- embryonic mice on day 14 of gestation, and WT-NSCs and OTUD3-/--NSCs were cultured in vitro and subcultured according to cell status. After subculture to the third generation, an inverted microscope was used to observe the growth state of OTUD3-/--NSCs and WT-NSCs on days 1 and 3. Immunofluorescent staining was used to measure the expression of Ki67, Nestin, and β-tubulin Ⅲ in WT-NSCs and OTUD3-/--NSCs, and Western blotting was used to measure the changes in the expression of OTUD3 and Cx43 in WT-NSCs,OTUD3-/--NSCs, and the cerebral cortex of WT and OTUD3-/- embryonic mice. Results WT-NSCs and OTUD3-/--NSCs cultured and subcultured to the third generation showed a good growth status, and immunofluorescent staining showed positive staining of Ki67, Nestin, and β-tubulin Ⅲ. Compared with WT-NSCs,OTUD3-/--NSCs had significant reductions in the expression levels of OTUD3 and Cx43 (t=16.82,3.21,P<0.05), and compared with WT embryonic mice,OTUD3-/- embryonic mice also had significant reductions in the expression levels of OTUD3 and Cx43 in the cerebral cortex (t=10.04, 20.41,P<0.05). Conclusion The expression of Cx43 in NSCs is significantly downregulated after OTUD3 knockout, and Cx43 may play a regulatory role in promoting the proliferation of NSCs and neurodevelopment.